Quru’ in the Waiting Period (Iddah): A Comparative Analysis of the Hanafi and Shafi'i Schools of Thought - Imam Faishol (Al-Mahkamah: Islamic Law Journal, 2025)
The meaning of the term quru’ in Surah al-Baqarah verse 228 has long been a subject of classical debate among Islamic jurists, particularly in determining the duration of the iddah for women who have been divorced. The Hanafi and Hanbali schools interpret quruʾ as the menstruation period, whereas the Shafi’i and Maliki schools interpret it as the period of purity. These differing interpretations lead to variations in calculating the end of the iddah, which in turn have legal implications for the woman’s post-divorce status, the validity of reconciliation (ruju’), and legal certainty within the family law system. This article aims to comparatively analyze the views of the two major schools, Hanafi and Shafi’i, using a normative-textual approach while also considering the objectives of Islamic law (maqasid al-shari’ah). The analysis reveals that both schools present strong arguments based on linguistic evidence, hadith, and considerations of public interest (maṣlaḥah), reflecting the richness and dynamism of Islamic legal thought Keywords: Quruʾ, Iddah, Hanafi School, Shafi’i School, Islamic Family Law